2017
DOI: 10.14720/aas.2017.109.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation with nutrient solutions mixed with treated wastewater on Asiatic lily ‘Brunello’ grown in a closed soilless culture

Abstract: A plastic greenhouse study was implemented to evaluate the potential use of treated wastewater for irrigation of Asiatic lily 'Brunello' grown in zeolite. Plants received the following treatments: a nutrient solution (N) alone, (N) mixed with treated wastewater (W) at rates of 3N:1W, 1N:1W and 1N:3W respectively. A closed system was used in which the drain solution was circulated for several days until its electrical conductivity reached 2.3 dS m -1 , after which fresh irrigation solutions were used to start a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Water requirements are linked to climate and production system, for example, it has been noted that in tropical climates roses show stem thickening and water stress problems, which can be mitigated under greenhouse conditions. Some authors recommend maintaining water content in soil stresses close to 3 kPa (Almeida et al, 2012;Oki et al, 2001), this also results in better flower quality, but the worst results were observed for stresses above 15 kPa (Al-Hammouri et al, 2017). We have also experimented with the use of low quality water (saline), evaluating the quality of roses (Rosa indica, Rosa canina and Natal Briar) and carnations Voyore, Diana and Chad, with promising and not very limiting results from the production point of view (Tsirogiannis et al, 2010).…”
Section: Irrigation and Water Resource Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Water requirements are linked to climate and production system, for example, it has been noted that in tropical climates roses show stem thickening and water stress problems, which can be mitigated under greenhouse conditions. Some authors recommend maintaining water content in soil stresses close to 3 kPa (Almeida et al, 2012;Oki et al, 2001), this also results in better flower quality, but the worst results were observed for stresses above 15 kPa (Al-Hammouri et al, 2017). We have also experimented with the use of low quality water (saline), evaluating the quality of roses (Rosa indica, Rosa canina and Natal Briar) and carnations Voyore, Diana and Chad, with promising and not very limiting results from the production point of view (Tsirogiannis et al, 2010).…”
Section: Irrigation and Water Resource Managementmentioning
confidence: 99%
“…Research has also been conducted on the cultivation of Asiatic lily 'Brunello', specifically evaluating irrigation in zeolite and a mixture of treated water (Al-Hammouri et al, 2017). The results indicated that the concentration of treated water for irrigation, depending on the concentration, has an effect on crop development, however, it is possible to achieve quality standards when a balance of concentrations is found.…”
Section: Irrigation and Water Resource Managementmentioning
confidence: 99%
“…The aeroponic baskets are made of plastic and grooved with a total volume of 232.26 cm 3 , filled with Arlite (inert material) for the development of the root. Lilium 'Tresor' was selected as the cut flower because it has a commercial market and also, it has shown tolerance to irrigation with water with an electrical conductivity of up to 2.3 dS/m [25]. The experimental units were installed in the experimental station of the Center for Research and Development in Water Resources (CIDERH) in the city of Iquique, in the north of Chile, in the coastal Desert of Atacama, and separated from the outside only by an anti-aphid mesh and without temperature regulation.…”
Section: Experimental Designmentioning
confidence: 99%